Synthesisation of Photo-Mechanoluminescence Crystal of Europium Dibenzoylmethide Triethylamine (EuD4 TEA) with Different Solvent - Suriani Abu Bakar, Azmi Mohamed (Tanjung Malim, 2024)
Synthesisation of Photo-Mechanoluminescence Crystal of Europium Dibenzoylmethide Triethylamine (EuD4 TEA) with Different Solvent by Suriani Abu Bakar, Azmi Mohamed